2002
DOI: 10.1042/bst030a072b
|View full text |Cite
|
Sign up to set email alerts
|

Genotype/phenotype correlation in patients with Erythropoietic Protoporphyria

Abstract: Homocysteine (Hcy) is a sulphur containing amino acid, derived from the metabolism of methionine. Elevated Hcy plasma concentrations result in hyperhomocysteinemia, a risk factor for cardiovascular disease. The causes are genetic defects of the key enzymes, acquired conditions, or a combination of both. In this study we assessed the effects of nitric oxide on Hcy, cysteine (Cys) and cysteinal-glycine (Cys-Gly) production by the rat hepatoma HTC cells, using the NO-donor, diethylamine NO-NOate (DEA-NO). D E A -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…24 In Argentina, Parera detected three novel and two previously described mutations in five Argentinean EPP families; (1) a deletion (451delT) producing a stop codon located 18 codons downstream from the mutation, (2) IVS1-2A>G leading to exon 2 skipping, (3) IVS4-2A>G, which causes the loss of the first 48 bp of exon 5, (4) C343T, and (5) 400delA. 25 Colombo's study of 19 Argentina EPP patients identified three novel (p.S222N; p.R298X and p.R367X) and seven already known (g.12490_18067del; p.R115X; p.I186T; c.580_584delTACAG; c.598+1G>T; p.Y209X and p.W310X) and indicated the possibility of c.315-48C variant in trans to the mutated allele as a sufficient trigger of EPP. 15 In Spain, Herrero reported that three novel mutations (IVS4+1delG, 347-351delC, and 130_147dupl 18) and IVS3-48C low-expression allele in ten of 11 EPP patients.…”
Section: Genetic Characteristics Of Eppmentioning
confidence: 99%
“…24 In Argentina, Parera detected three novel and two previously described mutations in five Argentinean EPP families; (1) a deletion (451delT) producing a stop codon located 18 codons downstream from the mutation, (2) IVS1-2A>G leading to exon 2 skipping, (3) IVS4-2A>G, which causes the loss of the first 48 bp of exon 5, (4) C343T, and (5) 400delA. 25 Colombo's study of 19 Argentina EPP patients identified three novel (p.S222N; p.R298X and p.R367X) and seven already known (g.12490_18067del; p.R115X; p.I186T; c.580_584delTACAG; c.598+1G>T; p.Y209X and p.W310X) and indicated the possibility of c.315-48C variant in trans to the mutated allele as a sufficient trigger of EPP. 15 In Spain, Herrero reported that three novel mutations (IVS4+1delG, 347-351delC, and 130_147dupl 18) and IVS3-48C low-expression allele in ten of 11 EPP patients.…”
Section: Genetic Characteristics Of Eppmentioning
confidence: 99%